Security Enhancement through Cryptography and Hardware Devices - Devi, Aruna T; Majjigi, Tejaswini S (International Journal of Computer Sciences and Engineering, 2025)
Security is being a hot topic in present digital era. The growing usage of technology for communication generates data which is available everywhere but data security is the important issue which draws the attention of all. Cryptography and security is a notion to secure the network and information transmission through wireless network. With ever progression in digital system security has been appeared as a major concern. In this era of virus and hackers of electronic bugs and electronic fraud security is primary. The concept of hardware security has been normally related with the cybersecurity and cryptography. Cyber-attacks are usually more due to lots of users connected to the internet. The basic issues in guarding the safe transmission of data through the web are concern of the security. This paper emphasizes on the key concepts of cryptography and security on critical infrastructure devices to overcome the threats of computer network security.